VALUASI NILAI EKONOMI HUTAN DAN NILAI EKONOMI PERTAMBANGAN TIMAH DI KABUPATEN BANGKA TENGAH - , IRVINDIO PATRIANUSA, Retno Widodo Dwi Pramono, S.T., M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2014)
There is a tendency that exceeds the conversion result in the loss of biodiversity in forests. This will trigger the vulnerability of natural conditions accompanied by a decline in the quality of land erosion, pests, and diseases. Tin mining industry in addition to bring in foreign exchange and employment siphon also almost certain to have a negative impact on the environment. Negative impacts include the ground motion that can take its toll both property and lives, the loss of water catchment areas in the hills, landscape destruction, siltation in the river that could impact to downstream, increasing the intensity of erosion in hilly areas, road-of the road transport vehicle mines material becomes damaged, disrupting groundwater conditions, and the occurrence of large pools of water when excavations in the plain areas, as well as affecting the social life population around the mine site. Economic valuation methods used in this study is based on the market price approach, and benefits transfer. The economic value of forests is smaller than the economic value of tin. However, many negative externalities are often overlooked. For example, the benefits of a tin mine only up to 15 years. After that the tin mines no longer provide benefit to the community because the content of lead discharged. Meanwhile, if the forest continues to be considered will continue to provide many benefits, even though the economic value of the calculation is smaller than the tin mines. So we can conclude benefits of forests and sustainable long term when compared to tin. The results of this study can be used as a reference in determining the pattern space. Looking at the results of this study, better serve the mining area into forest cultivation area. Because the region has a high value, longterm benefits, as well as sustainable. If the area is converted into mining would eliminate benefits contained therein.